PERAN ORANG TUA DALAM PENINGKATAN PEMAHAMAN AGAMA DALAM PENYIAPAN ANAK KE JENJANG PERNIKAHAN (STUDI KASUS DOSEN FAI UIKA BOGOR) - Zenal Mutaqin; Syarifah Gustiawati Mukri (KOLONI, 2022)
Marriage is one of the acts of worship that can perfect one's faith and piety. The purpose of a marriage that every couple wants to achieve is the creation of a sakinah, mawaddah and warohmah family. Based on the research that has been done, West Java is a province with a very high number of divorce cases from year to year. For example, in West Java, there were 55,876 divorce cases in 2020. There are indicators that lead to easy divorce, namely the lack of religious understanding which has an impact on the ease of taking divorce decisions. So, it is very necessary for the role of parents to improve children's religious understanding for their provisions to live a household life. The purpose of this study was to determine the background of increasing religious understanding by parents in children and to find out how the role of parents in increasing religious understanding to prepare their children for marriage. The researcher uses a qualitative research type with a case study approach. The research was conducted at the Ibn Khaldun University in Bogor on FAI lecturers. The results of the study show that the role of parents is to care for children with love, provide education including religious education, adab and moral education, education to read the Qur'an, economic education and pre-marital education, and provide materially. Keywords: the role of parents, religious understanding, children